Socio-economic factors affecting the rate of adoption of acacia plantations by smallholders in Indonesia. (July 2018) - Permadi, Dwiko B.; Burton, Michael; Pandit, Ram; Race, Digby; Ma, Chunbo; Mendham, Daniel; Hardiyanto, Eko B.
Abstract: Acacia plantations have an important role in increasing the reforestation rate and fulfilling the market demand for processed timber in some Asian countries. This study investigates the factors affecting the time-to-adoption of Acacia spp. by smallholders in different landscapes of Indonesia. We use discrete time duration analysis and data on time of first adoption by 430 landholders from Yogyakarta and the outer regions of South Sumatra and West Kalimantan. Results show that, on average, the time to adoption among smallholders in Yogyakarta was 3.1 years, while that for the outer regions was considerably longer at 10.8 years. Faster rates of acacia adoption were associated with smallholders growing other timber species, having larger land holdings, land acquired from inheritance (compared to via the market), being younger, having an on-farm occupation, and having experience of contracts used in commercial forestry. Changes in the reforestation schemes had limited impact on the adoption rate of acacia, although some schemes marginally decreased or increased the adoption rate. This could be associated with limited availability of acacia seedlings provided by government, which prioritizes seedlings of other commercial tree species, and changes in the contract mechanisms. The mode of extension, such as farmer-to-farmer learning and forest extension agents, also affected adoption.